2005
DOI: 10.1007/s10899-005-5555-5
|View full text |Cite
|
Sign up to set email alerts
|

The “Locals” Market: An Emerging Gaming Segment

Abstract: One of the newest customer segments to be identified by casino marketers is the "locals" market, or local resident gambler market. This study addresses the relative lack of empirical data on the "locals" market segment. The purposes of the study are to identify important reasons for visiting a particular casino; to identify which casinos respondents visit most often and why; to gain an understanding of such behavioral variables as gambling budget, time spent gambling, and favorite game; and to determine percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 12 publications
1
34
1
Order By: Relevance
“…(2001) compared the difference between slot players and table game players in terms of hedonic pleasure-seeking and found that table game players tend to get more enjoyment from hedonic factors that, for example, provide them absorbing experiences and satisfy sensation-seeking. Shoemaker and Zemke (2005) examined the major reasons that local residents visit casinos in Las Vegas and suggested that they chose casinos for practical reasons, such as accessibility and safety, rather than as a result of the promotional efforts of casinos. Abarbanel et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2001) compared the difference between slot players and table game players in terms of hedonic pleasure-seeking and found that table game players tend to get more enjoyment from hedonic factors that, for example, provide them absorbing experiences and satisfy sensation-seeking. Shoemaker and Zemke (2005) examined the major reasons that local residents visit casinos in Las Vegas and suggested that they chose casinos for practical reasons, such as accessibility and safety, rather than as a result of the promotional efforts of casinos. Abarbanel et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comparison of traveler demographics to Las Vegas and Atlantic City found that distance was the most important driver of visitation, but the research did not evaluate gaming behavior (Reece, 2001). Shoemaker and Zemke (2005) analyzed the Las Vegas local market to evaluate drivers of casino choice. Being an "easy drive from where I live" was the most important characteristic, while restaurant attributes ranked 7th and 8th most important out of 25 attributes.…”
Section: Market and Customer Characteristicsmentioning
confidence: 99%
“…These casinos have been largely unsuccessful in extracting revenue from neighbouring states. Unless these casinos attract a substantial number of international visitors, they should be regulated as though their markets were entirely local (Shoemaker and Zemke ).…”
Section: Discussionmentioning
confidence: 99%